"MUDA": SIMPLIFYING TRANSLITERATION AND TRANSCRIPTION OF ARABIC TEXT - Nurulasyikin Muda (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aims to propose a new system in Arabic romanization to simplify the typing process by using the QWERTY keyboard. The proposed system will be named as â€œMUDAâ€ as the main authorâ€™s surname and the name itself is nearly similar to the word â€œMUDAâ€H in Malay which mean easy or simple that represent the concept of the system. This is to facilitate the needs of the writers, and to decrease the gap of ambiguity for the systems created previously with the one that can increase the product of academic writing when dealing with Arabic romanization. The data of this study is analysed by finding the similarity within the previous transliteration systems and the phonetic system in English. Both systems then will be analysed by comparing them with the characters on the typing keyboard in terms of similarity. This study found that there are 23 keys will be used in 3 ways as follow; (i) single character typing excluding shift; (ii) shift + character (T, S, D, Z,â€); and (iii) combining character (th, sh, gh, kh, dz). This explains that no more complicated system of typing process will occur. Hence the speed of completing task in typing Arabic romanization will become faster.